The Effect of Training and Work Discipline on Employees Performance at PT. Astra Honda Motor - Novita Sari; Veithzal Rivai Zainal; Lenny Christina Nawangsari (Dinasti International Journal of Education Management And Social Science, 2023)
Every company engaged in the field of goods or services will pay great attention to the quality of human resources, because human resources are a company asset that needs to be maximized, to become the maximal form of human resources in institutions or companies, one of which is to conduct job training to increase employee abilities, knowledge, and skills. In addition, to conducting training, employees must also know about work discipline with the aim that employees are expected to work more quickly, effectively, and efficiently in their implementation so that these two elements will greatly affect performance, if the employee's performance is optimal then it will provide maximum output for the company. The purpose of this study is to see the impact of training and work discipline on employee performance at PT. Astra Honda Motor. Populations in this study are employees of PT. Astra Honda Motor in the production section. The total sample in this study is 67 employees. Data collection techniques in this study are literature, observation, interviews, and questionnaires. The analysis technique used is descriptive analysis and multiple linear regression analysis. This study concludes that training (X1) and work discipline (X2) have a positive and significant impact on employee performance (Y) at PT. Astra Honda Motor.